Higher education regionalism in Europe and Southeast Asia: Comparing policy ideas. Issue 1 (2nd January 2017) - Chou, Meng-Hsuan; Ravinet, Pauline
Abstract: Regional cooperation in the higher education policy sector has been on the rise throughout the last decades. In this article, we compare and analyse two instances of higher education regionalisms (i.e. political projects of higher education region creation) in Europe and South-East Asia from an ideational perspective. In so doing, we engage with and challenge the diffusion argument common in both European higher education studies ('Bologna Process export thesis') and new comparative regionalism. Using publicly accessible documents from regional bodies active in higher education policy coordination, and 53 semi-structured interviews with key policy actors involved in these developments, we identify the policy ideas of European and South-East Asian higher education regionalisms, and consider whether the extant models of regional cooperation and the knowledge discourse affected their evolution. Our findings indicate that the 'Bologna Process export thesis' and the diffusion assumptions of comparative regionalism are too simplistic and misleading. We conclude with suggestions for scholars interested in new comparative regionalism.